Dengue Fever as A Cause of Acute Disseminated Encephalomyelitis (ADEM) - Chowdhury, RN; Siddiqui, MR; Mahbub, MS; Hasan, OSI; Talukder, A; Nabi, S; Miah, T (Journal of Medicine, 2011)
Dengue fever is very common in Bangladesh. Every year a large number of urban populations suffer from this viral infection. Various presentations of dengue fever have been documented. Neurological complications in dengue fever are relatively uncommon. Among these, Acute Disseminated Encephalomyelitis (ADEM) has been observed in very few cases. Here we present a case of 13 year old girl suffering from ADEM following dengue fever. Keyword: Acute Disseminated Encephalomyelitis, Dengue fever, Neurological complication. DOI: http://dx.doi.org/10.3329/jom.v12i2.8428 JOM 2011; 12(2): 185-187